Schistosoma mansoni Infection Is Impacted by Malnutrition - Maciel, Poliane Silva; Gonçalves, Ricardo; Antonelli, Lis Ribeiro do Valle; Fonseca, Cristina Toscano (Frontiers in Microbiology, 2021)
Schistosomiasis remains one of the most important neglected tropical diseases in the world. It mainly affects developing countries, where it often coexists with malnutrition. Despite this, few studies have investigated the relationship between schistosomiasis and malnutrition. Herein, we evaluate the impact of malnutrition on experimental S. mansoni infection. Mice were divided into 5 groups: Control (Ctrl) diet (14% protein and 10% lipids), low-protein 3% (LP 3%), low-protein 8% (LP 8%), low-fat 2.5% (LF 2.5%) and low-fat 5% (LF 5%). Mice were fed with their respective diets and were infected when a difference of approximately 20% in the body weight between mice from any experimental group and mice from the control group was achieved. Nutritional, parasitological, and immunological parameters were assessed either just before infection and/or approximately 50 days later before mice were perfused. Our results showed that the 3% low-protein diet was the only one capable of establishing malnutrition in mice. Mice fed with this diet showed: (i) significant reduction in body weight and serum albumin levels before infection, (ii) decreased levels of all biochemical parameters evaluated before perfusion, (iii) decreased numbers of schistosome eggs trapped in intestines and impaired parasite fecundity, (iv) a delay in the granuloma development with a smaller granuloma area, and (v) reduced levels of IL-4 and IFN-γ in the liver. Our findings demonstrate that low protein supply leads to malnutrition in mice and impacts the cytokine milieu in the liver and granuloma formation. Additionally, the establishment of our murine malnutrition model will enable future studies aiming to better understand the complex relationships between nutrition, immune responses, and infection outcome.